Pengaruh Layanan Bimbingan Kelompok dan Materi Kemandirian Terhadap Peningkatan Konsep Diri Peserta Didik di UPTD SMP Negeri 7 Gunungsitoli - Midar Kristiani Zega; Famahato Lase; Hosianna Rodearni Damanik; Justin Foera-era Lase (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2026)
This study aims to determine the effect of group guidance services and self-reliance material on improving the self-concept of students at UPTD SMP Negeri 7 Gunungsitoli, using associative quantitative methods of multiple linear regression analysis. The population in this study were all 204 students and the sample was drawn by purposive sampling, namely class VIII-B as many as 23 students. Data were collected using questionnaire techniques using closed questionnaires, analyzed using multiple linear regression tests. The results of this study indicate that group guidance services with independence material have an influence in improving the self-concept of students, namely before the implementation of the service the self-concept of students is not good while after being given the service the self-concept of students becomes good and there is a significant influence both together and partially.